2015
DOI: 10.1016/j.devcel.2015.01.002
|View full text |Cite|
|
Sign up to set email alerts
|

Weaning Triggers a Maturation Step of Pancreatic β Cells

Abstract: Because tissue regeneration deteriorates with age, it is generally assumed that the younger the animal, the better it compensates for tissue damage. We have examined the effect of young age on compensatory proliferation of pancreatic β cells in vivo. Surprisingly, β cells in suckling mice fail to enter the cell division cycle in response to a diabetogenic injury or increased glycolysis. The potential of β cells for compensatory proliferation is acquired following premature weaning to normal chow, but not to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
126
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 52 publications
5
126
0
Order By: Relevance
“…Furthermore, recent work has observed that mice prematurely weaned to a high-fat diet resembling milk showed a lower increase in plasma insulin in response to glucose compared with mice prematurely weaned to a normal chow diet (Stolovich-Rain et al 2015). These data point to the leading role of diet over age in the maturation of the beta-cell GSIS.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, recent work has observed that mice prematurely weaned to a high-fat diet resembling milk showed a lower increase in plasma insulin in response to glucose compared with mice prematurely weaned to a normal chow diet (Stolovich-Rain et al 2015). These data point to the leading role of diet over age in the maturation of the beta-cell GSIS.…”
Section: Discussionmentioning
confidence: 52%
“…Previous works had shown that a physiological critical window that consists of the suckling and weaning periods plays a significant role in rat beta-cell development and lifespan function (Aguayo-Mazzucato et al 2006, CabreraVasquez et al 2009, Stolovich-Rain et al 2015. Research on the development, including the postnatal period, of pancreatic beta-cells could generate significant knowledge to, on one hand, improve the generation of mature insulin-producing cells as a source for diabetes cell-based therapies and, on the other hand, to stimulate in situ beta-cell division to overcome insulin deficiency observed during diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Human β-cells therefore have reached functional maturity by the age of 1 year, before expansion of their mass is complete. Closer timing of postnatal β-cell maturation and elucidation of its mechanisms will require studies of islets from infants between birth and the age of 1 year, particularly around weaning [45]. Ideally, functional and genetic approaches should be combined to determine whether increased expression or silencing of the same genes as in rodent β-cells [4547] impact on the secretory process.…”
Section: Discussionmentioning
confidence: 99%
“…Closer timing of postnatal β-cell maturation and elucidation of its mechanisms will require studies of islets from infants between birth and the age of 1 year, particularly around weaning [45]. Ideally, functional and genetic approaches should be combined to determine whether increased expression or silencing of the same genes as in rodent β-cells [4547] impact on the secretory process. The endeavor will be challenging owing to the rarity of infant donors, but should prove valuable for the numerous laboratories currently attempting to derive well-functioning β-cells from human pluripotent stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting a role for miRNAs in mediating the effects of nutrients on β-cell differentiation and function, Regazzi et al have recently demonstrated that the expression of several miRNAs such as miR-29b, miR-17 and miR-25, changes during the post-natal β-cell maturation that occurs at weaning (Jacovetti et al, 2015). Nutrient changes associated with weaning have been demonstrated to trigger complete β-cell maturation, at least in mice, required for adequate β-cell secretion and compensatory proliferation (Stolovich-Rain et al, 2015). …”
Section: Mirnas and β-Cell Responses To Stressmentioning
confidence: 99%